The Rate of Seller Correctness in Naming Batik Solo Pattern: Studied in Indonesia Online Marketplace - Berlian Rahmy Lidiawaty; Mohammad Isa Irawan; Raden Venantius Hari Ginardi (Jurnal Sosial Humaniora, 2020)
Every pattern in batik Solo has a different meaning that affects its use. Thereare patterns for cultural ceremonies, including funerals. Therefore, the sellerof batik Solo’s product has to be able to give the right title as the name of itsproduct in the online marketplace, so the customer will not miss wear thebatik in the wrong ceremony. According to the importance of naming batikSolo’s product, this study aims to assess the accuracy of batik Solo patternnaming by sellers in Indonesian online marketplace. Thus the result of it canbe used by the buyer as a recommendation where is the best marketplace topurchase the batik Solo product. First, the study collects the images samplefrom four biggest marketplaces in Indonesia; Tokopedia, Bukalapak, Shopeeand Lazada. The sample was collected by inputting the name of batik Solopattern in the marketplace’s search bar. The keywords that have been usedto collect the sample are batik Parang, batik Truntum, batik Sawat, batikKawung and batik Slobog. Those are the kinds of batik Solo pattern that hasdifferent expedience from each other. After 834 samples have been collected,the study assigns whether the seller give the correct name to the batik Soloproduct or not. The result of this study is the correctness percentage (CP) ofthe seller in naming their batik Solo product. In general, the CP is 82,13%,Marketplace with the highest CP is Lazada (95,42%) and the highest CP ofpattern is Parang (91%). Besides that, the study also rates marketplace withthe parameter of Best Marketplace by Pattern (BMP) and Best Marketplaceof Category (BMC). The study divided the parameters to rate marketplacebecause the best marketplace that has the highest correctness percentage inone category of a pattern is not always a marketplace that has the highestcorrectness percentage in that pattern.